Preventive Detection and Education to Realize Anti Bullying Friendly Schools - Meidi Saputra (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Bullying is a serious problem in the world of education. The case, which keeps popping up in various schools, requires commitment in handling it. One of the efforts to deal with bullying in schools is to make schools a friendly place for students. To achieve this, it is necessary to detect and prevent preventive education of students in schools. The purpose of this community service is to conduct early detection of bullying in schools and conduct preventive education about bullying. This service implementation method consists of 1) Situation Analysis, 2) Service Program Planning, 3) Service Implementation and 4) Service Evaluation. The result of this community service is that students gain knowledge about bullying in schools and the school through students who take part in the service, are committed to carrying out a positive anti-bullying campaign in schools to create friendly schools for school residents.